Triage of antenatal care through telehealth during COVID-19 pandemic in a tertiary care centre of North India - Amrit Gupta; Sangeeta Yadav; Malathy Seduchidambaram; Neeta Singh; Prasanta K Pradhan; Mandakini Pradhan (Journal of Family Medicine and Primary Care, 2022)
Background: Telemedicine facilitates patient care in various fields including antenatal care. Its application and usefulness need objectification and can be a guide to using this service in the care of pregnant women. Material and Methods: This was a prospective observational study conducted from May 2020 to December 2020. Following the telemedicine practice guideline of the country, 3,360 teleconsultations were sought by 862 antenatal patients. The duration of each call, an indication of referral and pregnancy risk stratification were noted. Further management was classified into three categories depending upon the need for an immediate hospital visit, no hospital visit or scheduled visit after at least 48 h after the first contact. Results: The antenatal cases were referred for either maternal, foetal or both indications in 24.7, 54.8 and 20.5% of the cases, respectively. Women were classified as low risk (61.6%), high risk (35.7%) and severe risk (2.7%). In 1.4% of the patients, history and review of the records could not be done through telemedicine. The average time spent was 16.6 min for the first contact and 3.1 min for subsequent contacts. Further management was done with immediate visits in 385 (45.3%), scheduled hospital visits in 292 (34.3%) women and no tertiary care hospital visit in 173 (20.4%). Discussion: Women (20.4%) not called to the maternal-foetal medicine department of the institute were managed along with the treating obstetrician and no difference in pregnancy outcome was noted. Conclusion: Antenatal care can be provided following triage over teleconsultation and 1.4% of the women may not be able to use telehealth.